Answer:
In algebraic terms this means x-17>33
Step-by-step explanation:
to solve it x−17>33
1 Add 17 to both sides.
x>33+17
2 Simplify 33+17 to 50
x>50
Answer:
Below
Step-by-step explanation:
● f(x) = -2x + 3
● f (0) = -2 (0) +3 = 3
● f(-32) = -2(-32)+3 = 64 + 3 = 67
● f(10) = -2(10) +3 = -20 + 3 = -17
● f(-17) = -2(-17) + 3 = 34 + 3 = 37
● f(10) => -17
● f(-17) => 37
Answer:
y=-15
Step-by-step explanation:
Answer:
1 Chair= $1.25 1 table= $8.25
Step-by-step explanation:
5c+3t=31
2c+6t= 52
-2(5c+3t=31)
-10c-6t=-62
+
2c+6t=52
= -8c=-10
/-8 /-8
c= 1.25 or 1 1/4
2c+6t=52
2(1.25)+6t=52
2.5+6t=52
-2.5 -2.5
6t= 49.5
/6 /6
t= 8 1/4